Bridging the Digital Divide : Ensuring Access to Technology in Education for All Children - Aiman Danial; Aiman Hakim Rafiq; Farhan Izzuddin (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
The digital divide continues to be a barrier to equitable access to education, especially in underprivileged regions. This paper explores strategies to bridge the gap in digital technology access for children, focusing on the role of governments, non-profits, and private sectors in ensuring equal opportunities for digital learning. Case studies from various countries are presented, highlighting successful initiatives and challenges faced in providing technological resources to underserved communities.